2011
DOI: 10.1039/c1cp20488b
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of rhombic dodecahedral AgX/Ag3PO4 (X = Cl, Br, I) heterocrystals with enhanced photocatalytic properties and stabilities

Abstract: Herein, we have developed a facile and general method for the high-yield fabrication of AgX/Ag(3)PO(4) (X = Cl, Br, I) core-shell heterostructures with an unusual rhombic dodecahedral morphology, which exhibit much higher photocatalytic activities, structural stabilities and photoelectric properties than pure Ag(3)PO(4) crystals in environment and energy applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
289
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 530 publications
(307 citation statements)
references
References 42 publications
17
289
1
Order By: Relevance
“…The double-transfer mechanism is a common separation process for a large amount of composite photocatalysts, such as Ag2O/g-C3N4 composites [22]. If the Ag3PO4/g-C3N4 heterojunctions follow this mechanism, the schematic diagram of Ag3PO4/g-C3N4 can been seen in Figure 13a, as the potentials of the CB and VB edges of the g-C3N4 are −1.30 eV and +1.40 eV (vs. NHE), respectively, and the CB and VB edge potentials of the Ag3PO4 are +0.45 eV and +2.90 eV (vs. NHE), respectively [52,53]. Electrons in the CB of g-C3N4 would transfer to that of the Ag3PO4, and the holes accumulate on the VB of g-C3N4.…”
Section: Proposed Mechanismsmentioning
confidence: 99%
“…The double-transfer mechanism is a common separation process for a large amount of composite photocatalysts, such as Ag2O/g-C3N4 composites [22]. If the Ag3PO4/g-C3N4 heterojunctions follow this mechanism, the schematic diagram of Ag3PO4/g-C3N4 can been seen in Figure 13a, as the potentials of the CB and VB edges of the g-C3N4 are −1.30 eV and +1.40 eV (vs. NHE), respectively, and the CB and VB edge potentials of the Ag3PO4 are +0.45 eV and +2.90 eV (vs. NHE), respectively [52,53]. Electrons in the CB of g-C3N4 would transfer to that of the Ag3PO4, and the holes accumulate on the VB of g-C3N4.…”
Section: Proposed Mechanismsmentioning
confidence: 99%
“…The morphology modification, including controls of the size, shape, and surface structures, determines the chemical reactions efficiency and selectivity in heterogeneous photocatalysis through changing some physicochemical properties, such as face-specific reactant molecular adsorption and interfacial charge transfer [222][223][224][225][226][227][228][229]. Therefore, morphology modification is an important variable that should be deliberately designed to achieve prompted photocatalytic properties.…”
Section: Modification Of Morphologymentioning
confidence: 99%
“…Therefore, it is highly desirable to develop effective strategies to improve the stability of the Ag 3 PO 4 photocatalyst. Recent reports indicated that AgX (X=Cl, Br, I) nanoshells on the surface of Ag 3 PO 4 can enhance their photocatalytic properties and stability 23 . Furthermore, carbon quantum dots 24 , graphene oxide 25,26 , TiO 2 [27] , Bi 2 MoO 6 [28] , SnO 2 [29] and Fe 3 O 4 [30] were successfully used to form Ag 3 PO 4 based hybrid nanostructures for getting enhanced photocatalytic activity and stability.…”
Section: Introductionmentioning
confidence: 99%